The impact of governance and ownership structure on disclosure patterns transcending major regulatory change in Malaysia - Ho, Poh-Ling; Taylor, Grantley (Virtus Interpress, 2014)
The purpose of this study is to investigate the extent of voluntary disclosures between 2006 and 2009 that transcends major regulatory and governance changes in Malaysia and to assess the association between strength of corporate governance structure, and ownership structure on the extent of voluntary disclosures of Malaysian listed firms over that period. The average level of voluntary disclosure within the annual reports of sample firms increased over the two periods. Further, the extent of voluntary disclosure is significantly positively associated with strength of corporate governance structure in both 2006 and 2009. Firms with concentrated ownership structure are associated with more extensive voluntary disclosures. These findings highlight the importance of an effective governance regime and concentrated ownership structure in reducing information asymmetry and agency costs and thereby enhancing the level of voluntary disclosures. These findings also have practical implications for policy-makers, analysts, auditors and regulators in Malaysia as well as East Asian countries.